Glutaraldehyde/Polyvinyl Alcohol Crosslinked Nanosphere Modified Corn Stalk Reinforced Polypropylene Composite. (February 2019) - Liu, Shanshan; Ge, Heyi; Zou, Yu; Chen, Juan
Abstract: In this paper, polypropylene (PP) based wood-plastic composite (WPC) was prepared from corn straw fiber (CSF), and a new green way was found for the treatment of agricultural waste. In order to improve the interfacial compatibility between CSF and PP matrix, the glutaraldehyde (GA) and polyvinyl alcohol (PVA) crosslinked modified CSF was used. GA and PVA were crosslinked to form polymer particles on the surface of CSF. The WPC was characterized by SEM, FTIR, XRD and electronic universal testing machine. When the loading of modified CSF was 30 wt%, the flexural strength of WPC was up to 62 MPa, which was 12.3% higher than that of WPC reinforced by untreated CSF. Meanwhile, the composite reinforced by modified CSF had lower water absorption compared with that of the untreated CSF composite.